COVID-19 pandemic: a reminder to develop forensic radiology facility - Tanuj Kanchan; Ashish Saraf; Kewal Krishan; Binit Surekha; Pawan Garg; Sanjeev Misra (Journal of Infection in Developing Countries)
COVID-19 outbreak has resulted in a substantial morbidity and mortality, and has put the health system under tremendous stress. A need for devising and adopting newer methods and techniques is being emphasized in the healthcare facilities to combat the effects of the SARS-CoV-2. Besides patient care, focus needs to be laid on the effective and dignified management of the deceased and medico-legal services provided by the hospitals and medical institutions during the COVID-19 pandemic. Considering the likelihood of forensic experts and autopsy personnel being exposed to SARS-CoV-2 inadvertently during the autopsy, it is recommended to resort to safer and minimally invasive techniques of postmortem examination of the dead. In this regard, employing radiological techniques for postmortem examination appears to be a promising option during the COVID-19 pandemic. An inherent advantage of postmortem radiography over conventional autopsies is the minimization of the risk of transmission of infection to the health care workers. Our correspondence highlights on the possibility of using radiological facilities as an effective replacement of high-risk conventional autopsy procedures during the COVID-19 pandemic.